A Snapshot of RTI Implementation a Decade Later: New Picture, Same Story. (September 2020) - Berkeley, Sheri; Scanlon, David; Bailey, Tessie R.; Sutton, Jason C.; Sacco, Donna M.
Response to intervention (RTI) has evolved from its first decade of implementation. Because states guide and regulate policy and practice at the state and local education agency levels, it is important to understand their critical role in RTI implementation. A systematic review of all 50 state education agency websites was conducted to provide an updated "snapshot" of states' interpretation of RTI a decade after IDEA regulations were finalized. Findings revealed substantive progress towards developing approaches to systematic supports to students, with a major trend in adoption of multi-tiered system of support (MTSS) models. Findings also documented continued variation in how states are communicating about tiered systems on such matters as the roles of tiered systems in schoolwide prevention frameworks, meeting special education requirements, and aligning multiple systems within schools. Implications for special education services for students with learning disabilities are discussed.